SOME MINERALOGICAL ZONING FEATURES OF IRON ORE RIEBECKITE METASOMATITES IN THE KRYVYI RIH BASIN - Streltsov, V.; Evtekhov, V.; Evtekhova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Sodium metasomatism relates to epigenetic geological processes that had substantial impact on mineralogical indicators and washability of metamorphogenic low-grade magnetite ores (magnetite quartzites). It led to the formation of aegirine and riebeckite metasomatites, represented in productive strata of six out of nine iron ore deposits, exploited by four out of five Iron Ore Mining and Processing Works in the Kryvyi Rih basin. Riebeckite metasomatites, formed at relatively low thermodynamic factors of mineral formation medium, have much larger distribution in comparison to aegirine ones, that are 90 and 10% respectively of the total volume of metasomatic bodies. Riebeckite metasomatites, analyzed in this paper, have the maximum thickness provided their formation took place in strata of silicateless micaceous hematite-magnetite (up to 100 m, 56 m in average) and magnetite (up to 70 m, with an average of 47 m) quartzites, which make up the central part of the ferruginous horizons of the Saksagan suite. Bodies of riebeckite (magnesioriebeckite) metasomatites of significantly lower thicknessup to 30 and up to 15 m (19 m and 8 m in average) respectively were formed from cummingtonite-magnetite and magnetite- cummingtonite quartzite of peripheral zones of horizons. Despite the mineral composition of initial magnetite quartzites, the bodies of riebeckite metasomatites are characterized by similar internal structure. The rear zone, which is adjacent to the conduits supplying metasomatizing solutions, is represented by magnetite-riebeckite metasomatites. The intermediate zone consists of varying degrees of riebeckitized primary magnetite quartzites. Front zone, which is made up of the secondary quartzous magnetite quartzites, was formed as a result of a "run-down" of waste metasomatizing solutions rich in silica. Gradual transition to the unmodified magnetite quartzites is typical for the front zone. The main trend of mineralogical changes in magnetite quartzites due to sodium-metasomatosis was approximation of their composition to practically bimineral, that is magnetite + riebeckite (magnezioriebeckite), one. Riebeckite having composition close to the stoichiometric one, is typical for metasomatic rocks, which were formed within micaceous hematite-magnetite and magnetite quartzites. When riebeckitizing cummingtonite-magnetite and magnetite-cummingtonite quartzites mainly pseudomorphic replacement of cummingtonite by sodium amphibole occurred, the composition of the latter corresponds to magnesioriebeckite. The results of the mineralogical studies of riebeckite metasomatites are the basis for refining methods of geological, mineralogical, technological mapping of ore deposits, for correcting mineralogical and technological classifications of ores, for optimizing methods of ore homogenization before being fed to the processing plants.